Kepemimpinan Transaksional Kepala Sekolah Dalam Meningkatkan Mutu Pembelajaran Di Sekolah Dasar Negeri 9 Tilango Kabupaten Gorontalo - Mamonto, Resta; R. Mala, Abdurrahman; Sidik, Firman (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to identify the strategies, supporting factors, and obstacles in the transactional leadership of school principals in improving the quality of learning at SDN 9 Tilang. This study is a qualitative phenomenological study. This study uses interviews, observations, and documentation as research methods. The data analysis techniques used in this study consist of three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the principal's efforts to improve the quality of learning at SDN 9 Tilango include enhancing teacher professionalism through activities such as KKG (Teacher Working Groups), workshops, training programs, and professional development for teachers and educational staff to improve their teaching quality. Conducting supervision or monitoring of the learning process carried out by educators in the classroom. Providing motivation and guidance to teachers and educational staff and providing performance incentives for teachers. Supporting factors for the principal in efforts to improve teaching quality include the curriculum. Teaching conducted by teachers in the classroom is inseparable from the curriculum, which consistently assists teachers in their efforts to achieve good learning quality, as well as adequate facilities and infrastructure. A hindering factor is the shortage of administrative staff at SDN 9 Tilango, which also poses a challenge in improving learning quality. As a result, teachers are also serving as administrative staff.